Mutual Coupling Reduction between Two Closely Spaced Antennas with a General PMC Symmetry Plane for Mobile Terminals. (24th February 2023) - Fang, Yijiao; Zhong, Jiangwei; Nie, Yao; Fu, Maosheng
Abstract : In this paper, an artificial general perfect magnetic conductor (PMC) decoupling structure is proposed to improve the isolation between two-element closely spaced antenna arrays with an operating frequency around 2.4 GHz. This kind of PMC structure can effectively activate the in-phase coupling current and cancel the antiphase coupling current raised by the original perfect electric conductor (PEC) equivalent interface, thereby blocking the energy coupling from one antenna input port to another. The proposed design is composed of a transmission line and a lumped element in the neutral position of a pair of electrically small antennas. To validate the utility of this approach, we analyze the current/field distribution of this structure and the mode superposition mechanism in the present paper. The results show that, with a close center-to-center distance of 5 mm, the isolation between the arrays is improved from −5 dB to −20 dB at around 2.4 GHz. Furthermore, to validate the feature that this special in-phase coupling current distribution is insensitive to frequency, we analyze the decoupling performance in a frequency reconfiguration or a dual-frequencytwo-element antenna array. The decoupling feature emerges in the proposed structure over a larger frequency range (2.2–2.6 GHz) than the previous design. A sample of this two-element frequency reconfiguration antenna system is fabricated and measured in this paper. We also realized a dual-frequency antenna system with expected isolation. Through the above discussion, we can know that these decoupling geometrical parameters can be worked in the whole range of 2.2–2.6 GHz with the same decoupling structural parameters. Good performance and compact structures make the proposed structure suitable for mobile communication applications.